EVOLUTION OF THE UNDERSTANDING OF SOCIALLY RESPONSIBLE INVESTMENTS AND THEIR PERSPECTIVES - Дяковський, Дмитро (SWorldJournal, 2024)
The article analyse the essence of socially responsible investing, the key milestones of its development, foreign experience and current trends. Also the factors of appearance and spread of the given phenomenon, and modern principles used by socially resp